Explicit and Implicit Religion in Doctor Who and Star Trek - McGrath, James F. (Implicit religion, 2015)
It has often been proposed that the original series of Star Trek reflected a modern, enlightenment perspective on religion, and that subsequent spinoffs like Deep Space Nine moved in a more post-modern direction. Doctor Who, the longest running science fiction show, provides an interesting basis for comparison. Both television shows offer similar tropes, and in both instances, the rhetoric that claims to explain away religion in scientific terms ends up treating it as literally true. Both shows depict our universe as populated with "natural gods" which are sometimes explicitly identified with the gods and demons of ancient human religious literature.